REPRESENTATION, GENDER, AND PUBLIC POLICY: CONTEMPORARY PRACTICES IN INDONESIA - Sarah Novianti; Winda Eka Pahla Ayuningtyas; Hendika Dwinanda Wicaksana; Gema Pertiwi; Chomariyana Kartika Hesti (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
Studies on gender and state politics demonstrate that public policy is never gender-neutral but is shaped by power relations and social representations that normalize particular gender norms. In Indonesia, despite post-reform democratic consolidation and expanded political participation, gender inequality remains embedded in both the processes and substance of public policymaking. Existing scholarship has largely focused on formal political representation and affirmative policies, while the discursive and symbolic dimensions of policy formation have received limited attention. This article examines how gender is constructed and represented in Indonesian public policy through contemporary practices of social representation. Drawing on critical feminist policy analysis and an intersectional perspective, the study conceptualizes public policy as a site of meaning-making and power negotiation. The analysis reveals that public policies not only regulate resource distribution but also normalize specific gender roles and identities, often overlooking the diverse experiences of women across social locations. This article contributes to debates on gender and state politics by highlighting the importance of discourse and social representation in understanding and advancing gender-just and inclusive public policymaking in Indonesia